2013
DOI: 10.1111/1556-4029.12172
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Death Due to Hydatid Disease: A Six‐Year Study in the Northern Part of Tunisia

Abstract: Human ecchinococcosis also known as hydatid disease is a zoonotic infection caused by the tapeworm Ecchinococcus with 2-3 Million cases worldwide. We hereby report a 6 years period study of Sudden death due to hydatidosis aiming to analyze the epidemiological criteria, death circumstances, and autopsy observations attributed to hydatid disease. During the past 6 years, 26 death cases were due to hydatid disease. Our analysis shows that the sex ratio (M/F) was 1.6, the mean age was 31-year old, and 65% of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 28 publications
0
18
1
Order By: Relevance
“…Hydatid cystic rupture was reported to be a potential cause of sudden unexpected deaths, especially in young adults and children (9). Research also reported that hydatid cystic rupture may be spontaneous in young people who have a history of frequent trauma (10).…”
Section: Discussionmentioning
confidence: 99%
“…Hydatid cystic rupture was reported to be a potential cause of sudden unexpected deaths, especially in young adults and children (9). Research also reported that hydatid cystic rupture may be spontaneous in young people who have a history of frequent trauma (10).…”
Section: Discussionmentioning
confidence: 99%
“…It is a miracle that only this calcified cyst survived and was carefully picked up with the rest of her bones after the pyre cooled down. Anaphylactic shocks occur frequently (Khelil et al ., ), in particular during pregnancy because of decreased immunological responses (Abu Eshi & Ali, ). Her earrings ( ενώτια ) decorated with molossus‐type dogs made of semi‐precious stones may serve as indirect evidence that it was her love of Canis familiaris that led her to an early death.…”
Section: Discussionmentioning
confidence: 99%
“…[1,3,4] The world's major endemic regions are the Mediterranean Basin, South America, Asia, including India, Afghanistan, Iran and Turkey; and parts of East Africa. [1][2][3] Indeed the total number of infested subjects is estimated at 2-3 million worldwide [5] and the severity of this disease lies mainly in its acute complications (rupture, superinfection, anaphylactic shock, etc.) with a risk of sudden death attributed to this parasitosis which remains today "serious and not exceptional".…”
Section: Introductionmentioning
confidence: 99%
“…[6] This mortality mainly affects young people. [5,6] Brain localizations are part of the so-called unusual or aberrant localizations of this parasitosis (extra-hepatic and extra-pulmonary) observed in less than 10% of cases. [7,8] The psychiatric manifestations revealing cerebral hydatid cyst remain exceptional and often unrecognized and neglected by practitioners despite their potential severity.…”
Section: Introductionmentioning
confidence: 99%